Time and motion study in the industry 4.0 era: A systematic review of the literature - Sotsek, Nicolle Christine; Vivan, Marina Fernandes; De Oliveira, Aline Raquel (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose: the article aims to identify the main methods and tools used to study time and motion applied in the industry over the last 10 years. Theoretical framework: with Industry 4.0 and the new technological tools, time and motion studies gain new methods of application. With this, given that the market is intensely competitive, to know the methods and tools used to apply it in companies over the last 10 years can give organizations a competitive edge. Design/Methodology/Approach: This study is a systematic review of the literature – SRL. Analyzing articles found in Science Direct and on the Capes Website. International articles were chosen by searching terms and using established filters. Findings: As a result, it was noted that, despite the importance of its effects, there are few academic papers written in the area being studied. The review incorporated 31 articles that have been published since 2010, which contained content related to the application of the concept. Two types of study were found: those that apply the time and motion study tool using stopwatches, clipboards and direct observation, and research that has been applied virtually. Research, management & social implications: knowing the main methods and tools used in the study can improve the productivity of companies and the ergonomics of its employees, as well as assisting in constructing future research in the area. Originality/Value: The study presents the development of the theme from Taylorism to the digital age, as well as the main methods and tools used by companies, which are important for the management of organizations and their competitiveness. Key words: Study of times and movements; Work analysis; Chronoanalysis; Industry 4.0; Digital Age.